Long‐term effects of mulching, traditional cutting and no management on plant species composition of improved upland grassland in the Czech Republic. (3rd February 2019) - Gaisler, Jan; Pavlů, Lenka; Nwaogu, Chukwudi; Pavlů, Klára; Hejcman, Michal; Pavlů, Vilém V.
Abstract: A shortage of available livestock for utilizing grassland biomass in Central Europe is challenging for the management of both semi‐natural grasslands and previously intensified (limed, fertilized and reseeded) upland grasslands. An alternative method of grassland management is mulching, in which aboveground biomass is cut, crushed and subsequently spread on the surface. This paper reports on an experiment to compare three different mulching frequencies (one, two and three times per year) with an unmanaged treatment and traditional management of two cuts per year (control) on a previously improved upland meadow. Plant species composition was monitored over 13 years. Traditional management of two cuts with biomass removal was the most suitable method for maintaining plant species richness and diversity, and both were reduced significantly in the once‐mulched and especially in the unmanaged treatment. Tall dicotyledonous weeds such as Urtica dioica, Cirsium arvense and Aegopodium podagraria were promoted by the unmanaged treatment and by mulching once a year. Higher frequency of defoliation had positive effects on the spread of short forbs such as Taraxacum spp., Plantago lanceolata and Trifolium repens . After eight years, there were changes in sward structure in the unmanaged and mulched‐once‐a‐year treatments, with increase in the tall/short species ratio. In conclusion, repeated mulching cannot substitute fully for traditional two‐cut management in improved upland meadows without decreasing plant species richness and diversity, and changing the sward structure. Although mulching once a year may prevent invasion by shrubs and trees, it also supports the spread of weedy species similar to no management.